Aesthetic Response of Audiences’ Behavior of Dangdut Koplo Music Performance (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
Dangdut Koplo music performances are favored and watched by the public. This is able to generate an aesthetic response of the audiences, which is shown by their behavior. This study aims to examine the aesthetic response of audience behavior of dangdut koplo music performances in Pekalongan. This research uses qualitative methods, data collection using observation, interview, and document study techniques. Data analysis procedures used data reduction, data presentation, and data verification. The validity of the data used is triangulation, data sources, and theory. The results showed that the aesthetic response in the audience behavior of dangdut koplo music performance in Kalirejo village, Talun, Pekalongan Regency had a positive response that led to behavior, such as (1) dancing with friends in groups or alone; (2) Menyawer (giving some money); and (3) notice the show schedule. Based on the research results, it can be suggested: (1) can broaden the insight and description of the development of music, especially dangdut koplo music in the present era, (2) can be taken into consideration how the impact of dangdut koplo on the behavior of dangdut koplo music performances.